Reflection of V4 Interests in the Context of V4 Presidencies in the Enlarging and Reforming European Union as a Prerequisite for Agenda-shaping in Terms of the Netherlands - Slovakia - Malta (2016-2017) Presidency Troika - Kovačević, Dubravka
Predsedníctvo v Rade EÚ vs predsedníctvo vo V4: viacúrovňová vláda. Priebeh predsedníctva štátov vo V4 a vplyv Rady EÚ na jeho pôsobenie.